Microstructures: 3D Printing of Free Standing Liquid Metal Microstructures (Adv. Mater. 36/2013). (24th September 2013) - Ladd, Collin; So, Ju‐Hee; Muth, John; Dickey, Michael D.
<x xml:space="preserve">Abstract</x> A direct‐write method for writing 3D freestanding, liquid‐metal microcomponents from the binary eutectic alloy of gallium and indium at room temperature is described in work by Prof. Michael Dickey, Prof. John Muth, and co‐workers on page 5081. The smallest components fabricated by the technique are of the order of 10 μm in size, and smaller–sized structures may be possible. The technique allows the formation of mechanically stable structures and is capable of printing wires, spheres, arches, and interconnects. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>